Local origins: context, group identity, and politics of place - Wilcox-Archuleta, Bryan (2018)
In-group identity is particularly important in understanding political behavior among minority populations living in the United States. Despite its importance, we know relativity little about what explains variation in perceptions of group identity among U.S.-based minority groups. I develop a theoretical framework drawing extensively for social identity theory to explain development of in-group identities among Latinos in the United States. I suggest the availability of neighborhood-level ethnic stimuli increases the likelihood that Latinos will come to see themselves a part of pan-ethnic group rather than a unique individual. I use the 2008 Collaborative Multi-Racial Political Survey (CMPS), a nationally representative public opinion poll of registered voters with oversamples of Latino respondents. I find that the availability of ethnic stimuli positively associates with stronger perceptions of group identity among Latinos. Latinos who live in contexts rich with ethnic stimuli and cues are more likely to adopt in-group identities than those who live in environments lacking ethnically salient resources. - Reproduced.
Keywords: Group behaviour